A new reptile from the lower Permian of Brazil (Karutia fortunata gen. et sp. nov.) and the interrelationships of Parareptilia. (1st December 2020) - Cisneros, Juan Carlos; Kammerer, Christian F.; Angielczyk, Kenneth D.; Fröbisch, Jörg; Marsicano, Claudia; Smith, Roger M. H.; Richter, Martha
Abstract : A new parareptile from the Cisuralian Pedra de Fogo Formation of north-eastern Brazil is described. Karutia fortunata gen. et sp. nov. is the first Gondwanan member of Acleistorhinidae, a clade previously known only from North America but thought to be closely related to the Russian Lanthanosuchidae. A re-examination of parareptile phylogeny indicates that lanthanosuchids are not closely related to acleistorhinids. These results are more congruent both stratigraphically and biogeographically than the previous 'lanthanosuchoid' position for acleistorhinids, as they eliminate a 15 Ma ghost lineage within parareptiles, leaving Acleistorhinidae as an exclusively Pennsylvanian/Cisuralian clade from western Pangaea. Karutia fortunata contributes to our knowledge of the early Permian diversity of Parareptilia in Gondwana, a clade previously represented only by the mesosaurid inhabitants of the Irati-Whitehill epicontinental sea in the southern portion of the supercontinent. The new parareptile joins captorhinids in the amniote record of the Pedra de Fogo Formation, improving our picture of the inland tetrapod fauna of the southern hemisphere during the Cisuralian. http://zoobank.org/urn:lsid:zoobank.org:pub:79D59764-4DA0-4C28-B4D3-C517BBF64D81